Scanning Tunneling Spectroscopy Observation of Electronic Resonances Originating from 1 ×1 Potential on the Dense Pb Overlayer on Si(111) - Lu, Shin-Ming; Chan, Wen-Yuan; Chou, Hsing-Yi; Chiu, Ya-Ping; Su, Wei-Bin; Chu, Pei-Hong; Jiang, Chi-Lun; Chang, Chia-Seng; Hsiao, Hsi-Lien; Tsong, Tien Tzou (Japanese Journal of Applied Physics, 2012)
We use scanning tunneling spectroscopy (STS) to investigate the electronic structures of dense Pb overlayers of three phases grown on the Si(111) surface: the 1 ×1, √7 ×√3, and stripe incommensurate (SIC) phases. Although their atomic structures are all very different, the STS spectra of all three phases show nearly identical oscillatory features with two resonance peaks. These resonances are not common quantum-well states; they are energy bands originating from the dominant 1 ×1 potential in these phases. However, the local electronic states found by STS show that the resonance peaks are modulated with the superstructure of the √7 ×√3 phase, and that the resonance energy varies with the domains and the domain walls in the SIC phase.